The Impact of Multimodal Communication on Learners’ Experience in a Synchronous Online Environment: A Mixed-Methods Study - Cai, Ying; Pan, Zilong; Han, Songhee; Shao, Peixia; Liu, Min (Online Learning, 2022)
During the COVID-19 pandemic, from early 2020 onwards, the adoption of synchronous online learning increased rapidly. It offers students a unique learning experience, utilizing communication modes from both in-person and asynchronous online classes. This mixed-methods study examined the impact of modes of communication (visual, bodily behaviors, spoken language, and written language) found in synchronous online contexts on students’ learning experiences from the perspective of social presence and teaching presence, as well as their satisfaction with synchronous online learning experience. An online survey was distributed first to collect quantitative data. The survey results indicated that four different modes influenced students’ communication to a different extent, with written and spoken language being the most effective modes of online communication. These modes were also significantly positively correlated with social presence, teaching presence, and student satisfaction; however, only spoken language was a significant predictor of student satisfaction. In the qualitative phase, semi-structured interviews were conducted to examine students’ perceptions of how multimodality affects social presence, teaching presence, and satisfaction with online learning. This led to five major themes and highlighted how multiple modes of communication supports social presence, thereby helping teachers scaffold students. In addition, the online learning context impacts type of instruction, and the reduced distance between teachers and students improves teaching presence; however, the students felt a lack of affective belonging in their online classes. This study also provided implications for course instructors and designers to help them effectively adopt different modes in synchronous online environments and promote social and teaching presence.